CUSTODY PROCESSES WITH THE OCCURRENCE OF PARENTAL ALIENATION: AN ANALYSIS OF MEDIATION AS A SKILLED MEANS TO RESOLVE CONFLICTS (Reflection and Critique Law Magazine, 2023)
This article aims to investigate the possibility of parental alienation, how it happens, how the processes happen, how the motivation of the slanderous denunciation occurs. The manipulation exercised, usually by one of the parents, on a child or adolescent, against the other parent, characterizes the conduct of parental alienation. The alienating action is capable of generating serious psychological repercussions on those involved, who usually present a pattern of behavior, facilitating the identification of such cases. Once the occurrence of parental alienation is detected, measures capable of mitigating the effects of this practice must be adopted, such as the psychological treatment of the participants. In the event of inertia in relation to the impediment or mitigation of the consequences arising from the alienation process. Among the illicit most frequently reported maliciously, as a result of parental alienation, are mistreatment. In order to obstruct the beginning of the alienating action or, at least, prevent its continuation, Part of this work will make observations on some issues related to SAP and the mediation process between the parents to solve the problem configured in literature reviews. From this perspective, the prioritization of shared custody, the support of Guardianship Councils, the incidence of mediation, the specific criminalization of conduct, which would become a cause of increased penalty, are outlined in the fight against slanderous denunciation motivated by parental alienation. of the crime of slanderous denunciation. Hence the importance of conflict mediation for its minimization. Keywords: Parental alienation. Mediation. Slanderous denunciation.